Analysis of workability, mechanical strength and durability by the FT-IR method of concrete based on silica-limestone sand preserved in aggressive environments - Tarek Djedid; Mohammed Mani; Abdelhamid Guettala; Abdelkader Hima (Fracture and Structural Integrity)
The interest of using combined sand of equal percentage of silica and limestone becomes evident in the formulation of compacted concrete in several previous works around the world due to the formidable percentage of fines that improves the compactness and increases various mechanical resistances, which produces a more durable construction against different probable aggressions. This paper examines the effect of using this type of sand on workability, compressive strength, flexural strength, and splitting tensile strength. A durability test was consulted using infrared spectroscopy to assess diverse types of hydration products formed. The obtained results show clearly the advantages of using sand with silica and limestone grains (50/50)% in ordinary concrete infected by aggressive water. There is also an improvement in compactness, different mechanical resistances, and a reduction in the formation of harmful hydration products.